Penguatan Prodi Pengembangan Masyarakat Islam Berbasis Pendidikan Life Skills dan Teknologi Tepat Guna di Balai Latihan Kerja dan Industri Kabupaten Jember - Sofyan Hadi (Jurnal Al-Tatwir, 2019)
The Reinforcement of Islamic Community Development Study Program through community empowerment based on Life Skills Education and Intermediate Technology can be one solution to overcome unemployment while preparing prospective Community Development graduates. Moreover, life skills education and other intermediate technologies can serve as an alternative program which is able to provide appropriate basic training for students about the values of life and daily survival tips so that they are able and skilled to carry out the required things in life when they return to the society. From the description of the aforementioned issue, the researcher was intrigued to conduct a study by formulating the research objectives to achieve which were summarized in the general research problem namely The Empowerment of Community Development Study Program through Life Skills Education and Intermediate Technology. In order to achieve the research objectives, a research method was required as a concept and the base for analyzing and summarizing the research results. The current study employed a qualitative approach, while the type of the research was field research which can also be considered as a broad approach in qualitative research or as a method for collecting qualitative data. The reinforcement process of Islamic Community Development Study Program students in Faculty of Da'wah, IAIN Jember by BBLKI Jember Regency through life skills education included activities to foster activeness and to motivate students in choosing methods and media for life skills education accompanied with: Practical Activities and Evaluations. Meanwhile, for the tangible activities, there were small industries, small and medium scale entrepreneurship development, monitoring, life skills education, and intermediate technology. The Work and Industrial Training Empowerment Model in Jember was divided into three levels, namely micro, meso, and macro in which the approach was a combination of a task-centered approach, the use of groups as an intervention medium, and an empowerment directed at a broader environmental system.